2018
DOI: 10.1017/s0047404518000386
|View full text |Cite
|
Sign up to set email alerts
|

The sluttified sex: Verbal misogyny reflects and reinforces gender order in wireless China

Abstract: This article describes emerging misogynistic labels involving the morpheme biăo ‘slut’ as a gendered personal suffix in the Chinese cyber lexicon. We analyze the morphological, semantic, and cognitive processes behind their coinage, and the way they are used across gender lines in Chinese social media as a community of discourse practice. Our findings show that women participate in female pejoration as much as men do, and that men are more inclined than women to use pejorative labels that specifically attack f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Gender differences were mostly visible for the privacy invasion component of ATC (and to a lesser extent justice perceptions). Because gender discrimination (Woodhams et al, 2009) and sexism on social media (Jing‐Schmidt & Peng, 2018) are still prevalent in China, our findings suggest that female job seekers might rightfully be concerned with prospective employers accessing their profile. The positive relationship between extraversion and ATC is consistent with the conceptual definition of that personality trait (e.g., social self‐esteem and boldness; Lee & Ashton, 2018) and the fact that extroverts have more positive views toward social media in general (Bowden‐Green et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Gender differences were mostly visible for the privacy invasion component of ATC (and to a lesser extent justice perceptions). Because gender discrimination (Woodhams et al, 2009) and sexism on social media (Jing‐Schmidt & Peng, 2018) are still prevalent in China, our findings suggest that female job seekers might rightfully be concerned with prospective employers accessing their profile. The positive relationship between extraversion and ATC is consistent with the conceptual definition of that personality trait (e.g., social self‐esteem and boldness; Lee & Ashton, 2018) and the fact that extroverts have more positive views toward social media in general (Bowden‐Green et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…Chinese women are less likely to be assertive, confident, and to take control of their careers (Yi et al, 2015). Women are often the targets of verbal misogyny on Chinese social media (e.g., the term “biăo” or “slut” is used regularly on Weibo; Jing‐Schmidt & Peng, 2018). And, they are the target of employment discrimination (e.g., nearly 40% of job ads directly excluding women; Woodhams et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Individual identities in social media studies include gender, age, politician identities, among others. For example, Jing-Schmidt and Peng (2018) found that the male used the morpheme biăo (slut) as a gendered personal suffix in the Chinese cyber lexicon on Weibo to construct masculine identity of power. By focusing on instances of explicit and implicit references to age and aging of a Greek female user of Facebook, Georgalou (2015) argued that age identity is an interactive and collaborative process both facilitated and hindered by certain Facebook configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Another common discourse in all four cases demonstrates misogyny in Chinese online public discussion (Jing-Schmidt & Peng, 2018). Shaming and exclusion are made based on the targets’ gender—female, which is supposed to be irrelevant to the original discussion on patriotism.…”
Section: Discussionmentioning
confidence: 99%